2019
DOI: 10.1128/jvi.00172-19
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus 11 Early Protein E6 Activates Autophagy by Repressing AKT/mTOR and Erk/mTOR

Abstract: Low-risk human papillomaviruses (LR-HPVs) are the causative agents of genital warts, which are a widespread sexually transmitted disease. How LR-HPVs affect autophagy and the specific proteins involved are unknown. In the current study, we investigated the impact of LR-HPV11 early protein 6 (E6) on the activity of the autophagy pathway. We transfected an HPV11 E6 (11E6) plasmid into HaCaT cells, H8 cells, and NHEK cells and established a stable cell line expressing the HPV11 E6 protein. The differences in auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 76 publications
0
24
0
Order By: Relevance
“…Some studies showed that HPV16 entry requires clathrin-dependent endocytosis [ 22 25 ], however, other studies showed that HPV16 internalization requires tetraspanin-enriched microdomains for endocytosis, which was independent of clathrin [ 26 , 27 ]. Our previous study has revealed that HPV11 E6 induces autophagy by suppressing the AKT/mTOR and Erk/mTOR pathways, suggesting elevated autophagy level is beneficial for the survival of HPV11 in host cells after successful infection [ 28 ]. However, the host autophagic response during HPV11 entry has not been reported thus far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies showed that HPV16 entry requires clathrin-dependent endocytosis [ 22 25 ], however, other studies showed that HPV16 internalization requires tetraspanin-enriched microdomains for endocytosis, which was independent of clathrin [ 26 , 27 ]. Our previous study has revealed that HPV11 E6 induces autophagy by suppressing the AKT/mTOR and Erk/mTOR pathways, suggesting elevated autophagy level is beneficial for the survival of HPV11 in host cells after successful infection [ 28 ]. However, the host autophagic response during HPV11 entry has not been reported thus far.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were incubated with 1,000 vge/cell of HPV11 PsVs for indicated times and approximately 30 μg of cell lysate protein were subjected to western blotting protocols as described previously [ 28 ], using the following antibodies: polyclonal rabbit anti-LC3B (Cat#: L7543) and monoclonal mouse anti-actin (Sigma, Cat#: A9357), monoclonal rabbit anti-p62 (MBL Life science, Cat#: PM045), monoclonal rabbit anti-phospho-mTOR (Ser2448, Cat#: 2971), monoclonal rabbit anti-mTOR (Cat#: 2983), anti-phospho-70S6 kinase (Cat#: 9234), monoclonal rabbit anti-70S6 kinase (Cat#: 2708), monoclonal rabbit anti-phospho-4E-BP1 (Thr37/46, Cat#: 2855), monoclonal rabbit anti-4E-BP1 (Cat#: 9452), monoclonal rabbit anti-Erk (Cat#: 4695), monoclonal rabbit anti-phospho-Erk (Thr202/Tyr204, Cat#: 4370), monoclonal rabbit anti-Akt (Cat#: 4691), monoclonal rabbit anti-phospho-Akt (Ser473, Cat#: 4060), monoclonal rabbit anti-ULK1 (Cat#: 8054), monoclonal rabbit anti-phospho-ULK1 (Ser555, Cat#: 5869), monoclonal rabbit anti-phospho-ULK1 (Ser757, Cat#: 14202), monoclonal rabbit anti-AMPK (Cat#: 2603) and monoclonal rabbit anti-phospho-AMPK (Ser172, Cat#: 2531) (Cell Signaling Technology).…”
Section: Methodsmentioning
confidence: 99%
“…HPV can use different mechanisms to evade the proper autoimmune response of the host, through its oncoproteins (Tindle, 2002[ 151 ]). During infection two proteins (E6 and E7) are involved in the process of pathogenicity (Androphy et al, 1987[ 5 ]; Mesri et al, 2014[ 103 ]; Zhang et al, 2019[ 169 ]) (Figure 2 (Fig. 2) ).…”
Section: Hpv Oncoproteins and Signaling Pathwaysmentioning
confidence: 99%
“…HPV16 E7 has been shown to upregulate autophagy marker LC3B [ 135 ]. E6 is capable of activating autophagy by suppressing the mTOR (mammalian target of rapamycin) signaling [ 136 ]. The combination of E6 and E7 can increase the autophagosome cycle rate via ATG9B(Autophagy-related protein 9B) and LAMP1 (Lysosome-associated membrane glycoprotein 1) [ 137 ].…”
Section: The Role Of Atr Ddr In the Molecular Pathogenesis Of Hpvmentioning
confidence: 99%